Answer:
a)
First translating the graph of a along the x axis towards -2, and then along the y axis towards -3
b)
First we have to reflect the graph along the x axis and then translate it along thw y axis towards 4
Explanation:
Hi!
I will consider that ???? stands for g, so we have the fucntions:
h(x) = |x + 2| − 3
g(x) = −|x| + 4
a)
We can see that
h(x) = a(x+2) - 3
this means that we have to do two translations to get from the graph of a(x) to the graph of h(x).
the first one must occur along the x axis, where will the vertex be? we can figure this out looking for the point at which a(x+2) = 0, this point is x=-2, therefore, the first translation will be along the x axis towards -2.
The second translation is along the y axis, and the length of the translation is given evaluating h(x) at the point where a(x+2) vanishes, that is x=-2
h(-2) = -3
Therefore, the second translation will be along the y axis towards -3.
At the end, we will have the same a(x) graph but with its vertex at (-2,-3)
b)
here we can see that:
g(x) = -a(x) + 4
The minus sign multiplying a(x), indicates us that the graph must be reflected along the x axis, that is, insted of ''opening'' upwards, it will ''open'' downwards, the second tranformation is a translation along the y axis, and similar to the previous case, the point will be given when a(x)=0, that is:
g(0) = 4
therefore, the graph must be translated along the y axis towards y = 4